A Pair of Pharyngeal Gustatory Receptor Neurons Regulates Caffeine-Dependent Ingestion in Drosophila Larvae - Choi, Jaekyun; van Giesen, Lena; Choi, Min Sung; Kang, KyeongJin; Sprecher, Simon G.; Kwon, Jae Young (Frontiers in Cellular Neuroscience, 2016)
The sense of taste is an essential chemosensory modality that enables animals to identify appropriate food sources and control feeding behavior. In particular, the recognition of bitter taste prevents animals from feeding on harmful substances. Feeding is a complex behavior comprised of multiple steps, and food quality is continuously assessed. We here examined the role of pharyngeal gustatory organs in ingestion behavior. As a first step, we constructed a gustatory receptor-to-neuron map of the larval pharyngeal sense organs, and examined corresponding gustatory receptor neuron projections in the larval brain. Out of 22 candidate bitter compounds, we found 14 bitter compounds that elicit inhibition of ingestion in a dose-dependent manner. We provide evidence that certain pharyngeal gustatory receptor neurons are necessary and sufficient for the ingestion response of larvae to caffeine. Additionally, we show that a specific pair of pharyngeal gustatory receptor neurons, DP1, responds to caffeine by calcium imaging. In this study we show that a specific pair of gustatory receptor neurons in the pharyngeal sense organs coordinates caffeine sensing with regulation of behavioral responses such as ingestion. Our results indicate that in Drosophila larvae, the pharyngeal gustatory receptor neurons have a major role in sensing food palatability to regulate ingestion behavior. The pharyngeal sense organs are prime candidates to influence ingestion due to their position in the pharynx, and they may act as first level sensors of ingested food.